(untitled) (Dhaka University Journal of Biological Sciences, 2025)
This study explores the prevalence of different types of cybervictimization among 267 students at Dhaka University, Bangladesh, equally split between genders with a mean age of 22.61 (SD = 1.39) at various academic levels. Cyber victimization was measured using a Cybervictimization Questionnaire (reliability α = 0.72). The data was analyzed through Mann-Whitney U, frequency counts, and Chi-square tests using a convenient sampling technique. Results indicated no significant gender differences in experiencing cyber victimization (U = 10055.00, p = 0.068). The most frequent form was deliberate social media ignoring, reported often or always by 13.9% of students and rarely by 34.1%. Conversely, sharing assault videos was the least frequent, reported often or always by only 0.4% and rarely by 16.1%. Other significant forms included online impersonation, identity theft, password misuse, silent calls, offensive social media comments, spreading rumours, and exclusion from online communities. The statistical tests confirmed significant variability in cyber victimization experiences across different categories. This study highlights the specific cyber challenges faced by Dhaka University students, contributing to discussions on enhancing digital safety for young adults. Dhaka Univ. J. Biol. Sci. 34(2): 57-70, 2025 (July